Anti-diabetic effect of aloin via JNK-IRS1/PI3K pathways and regulation of gut microbiota - Ruting Zhong; Lanbin Chen; Yuanyuan Liu; Shouxia Xie; Sumei Li; Bin Liu; Chao Zhao (Food Science and Human Wellness)
This research aimed to investigate the antidiabetic activity, underlying mechanisms, and gut microbiota regulation of aloin. The insulin-resistant HepG2 (IR-HepG2) cell model and the type 2 diabetic (T2D) mouse model were successfully established using dexamethasone and a high-fat high-sucrose diet with low-dose streptozotocin, respectively. Aloin intervention increased glucose consumption and stimulated the activity of hexokinase and pyruvate dehydrogenase in IR-HepG2 cells. Additionally, it diminished the weight loss, reduced fasting blood glucose levels and hemoglobin A1c activity, and promoted glucose tolerance and fasting serum insulin activity in T2D mice. Histopathological analysis of the liver indicated hepatic protection by aloin. Additionally, aloin treatment inhibited the protein expression of c-Jun N-terminal kinases and activated that of IRS1/PI3K/Akt in the liver. Moreover, aloin modulated the bacterial community in the gut by raising the abundance of Bacteroidota and reducing the richness of Firmicutes, Proteobacteria, and Actinobacteriota. Thus, aloin ameliorated IR via activating IRS1/PI3K/Akt signaling pathway and regulating the gut microbiota, and it may be promising candidate as functional food for diabetic therapy.